Tree age and soil phosphorus conditions influence N2-fixation rates and soil N dynamics in natural populations of Acacia senegal - Isaac, M.E.; Harmand, J.M.; Lesueur, Didier; Lelon, J (Elsevier, 2011)
Acacia senegal, an important leguminous tree in arid and semi-arid environments, has shown promise as a multipurpose species, including gum production and soil fertility improvement, linked with N2-fixation capabilities. Of particular interest are ontogenetic and edaphic effects on A. senegal performance in natural populations. Our research objectives were to investigate the effect of tree age and site phosphorus conditions on (1) tree N2-fixation and (2) soil N and C dynamics in natural stands of A. senegal var. senegal, Baringo District, in the Rift Valley, Kenya. Sites consisted of A. senegal saplings (9 months) and mature A. senegal trees (7 years) along an edaphic gradient of soil P availability. A single-tree neighborhood approach was employed using a two by two factorial design: site conditions [high and low soil P contents] and tree age class [juvenile and mature]. Soil (N and C pools and fluxes) and plant metrics were quantified. A soil transfer experiment was also employed to confirm age and site effects on soil N mineralization. On the high soil P site, A. senegal had significantly lower foliar (15N levels than neighboring non-leguminous species (Balanites aegyptiaca), while foliar ?15N values in A. senegal on the low P site exhibited no significant difference with our reference plant, B. aegyptiaca. Across P sites, B. aegyptiaca had similar foliar ?15N values. These results indicate that the rate of N2-fixation of A. senegal trees, as determined with foliar 15N natural abundance methodology, increased with increasing soil P availability in these natural populations. However, N2-fixation rates declined with age. Although soil texture and soil CO2 efflux did not differ between sites or across ages, soils under mature A. senegal at the high P site exhibited significantly greater total N content and total C content in comparison to soils at the low P site and under juvenile plants. Furthermore, under mature A. senegal trees, soil N mineralization rates were significantly greater as compared to under saplings. Soil transplants confirmed that soil microbial activity may be stimulated under mature trees as N mineralization rates were 2 3 fold greater compared to under A. senegal saplings. Our findings suggest that tree age and soil P availability are important factors in the nitrogen budget of natural populations of A. senegal, determining N2-fixation rates, and potentially influencing soil total N and C pools and soil mineral N. This study provides information regarding the adaptation of A. senegal under differing edaphic conditions thus increasing accuracy of management support for A. senegal populations as productive agroforests.